CERPEN â€œPEMBALASANâ€ KARYA TASLIM NASRIN DALAM KAJIAN FEMINISME MULTIKULTURAL - Mateus Rudi Supsiadji (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2009)
Abstract. This article tries to discover the oppression undergoing by the female character, named Shamimma. The oppression is done by the male character named Suranjan. The oppression happens on the basis idea that Shamimma is a Muslim, the group of the people who Suranjan believe have kidnapped and raped her sister Maya. The discussion uses multicultural and glogal feminism criticism for what happen to Shamimma and Maya is among the problems that this criticism concerns with. Key words: feminisme multikultural, kekerasan seksual, kekerasan agama